THE INFLUENCE OF INDEPENDENT COMMISSIONERS, COMPANY COMPLEXITY, AND COMPANY RISK ON AUDIT FEES - Nurtania, Dwi; Adinda, Natasya; Fahira, Jihan; Zulman Hakim, Mohamad; Rachmania, Dewi (Accounting Study Program, Universitas Ciputra Surabaya, 2025)
This study aims to analyze the impact of independent commissioners, company complexity, and company risk on audit fees in technology sector companies listed on the Indonesia Stock Exchange during the period 2018-2022. Given the increasing dependence on technology and the increasing complexity in the business environment, understanding the factors that influence audit fees is very important. This study uses a purposive sampling method, where samples are selected based on certain criteria, and produces 8 companies with a total of 40 data. Data analysis was carried out using panel data regression techniques. Before the regression test was carried out, a hypothesis test was applied to ensure the validity of the model. The results of the study indicate that independent commissioners have no effect on audit fees, while company complexity has a positive effect on audit fees, and company risk has no effect on audit fees. These findings provide valuable insights for company management and auditors in managing and setting audit fees based on internal company factors.